Mapping of very shallow geothermal potentials in rural areas of Bavaria - Bertermann, David; Schwarz, Hans; Rammler, Mario; Jocic, Nikola (Glasnik Srpskog Geografskog Društva, 2024)
Climate change is a rising issue which strongly influences contemporary society. Therefore, the utilization of sustainable non-fossil energy sources is one of the most important goals in order to reduce greenhouse gas emission. Utilization of geothermal energy for heating and cooling buildings or residential units is one of the significant steps in providing sustainable and renewable energy supply. This paper presents very Shallow Geo-thermal Potentials (vSGP) of German federal state Bavaria, with special focus on rural are-as. Main goal of the study was to analyze the potentials for utilization of very shallow geo-thermal systems in terms of thermal conductivity and heat extraction. High-resolution soil maps containing information of grain size conditions served as an area-wide data basis for the research, while the analysis and visualization of the results were conducted by GIS software. Thermal conductivity as well as system-specific heat extraction were calculated depending on soil texture and climate conditions. Thermal conductivity results are intend-ed to be further used as the basic parameter for planning and installing horizontal geo-thermal heating and cooling systems.<br
Keywords: very shallow geothermal potentials (vSGP); thermal conductivity; heat extraction; sustainable cooling; rural area; Bavaria